Experiencing Food: Designing Dialogues : Proceedings of the 1st International Conference on Food Design and Food Studies (EFOOD 2017), October 19-21, 2017, Lisbon, Portugal /: Proceedings of the 1st International Conference on Food Design and Food Studies (EFOOD 2017), October 19-21, 2017, Lisbon, Portugal. (2018) - Unknown
No abstract available